Bioethical Principles of Use of Experimental Animals in Biomedical Research - Hidayat, Rachmat; Patricia Wulandari (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
A B S T R A C TResearch is an activity carried out based on scientific principles and methodssystematically to obtain information, data, and information from related subjects, withunderstanding the theory and proving assumptions and / or hypotheses. The resultsobtained are conclusions that can be applied or become additional knowledge for theadvancement of science. However, research activities must still respect the rights anddignity of research subjects. Health research includes biomedical, epidemiological,social, and behavioral research. Some health research can be done in vitro, usingmathematical models, or computer simulations.